Hermeneutic suspicion and silence in the archive? Reading the historiography on Don Diego de Torres, not the archive, against the grain - Cañizares, Jorge (2025)
Using the case of Don Diego de Torres, Muisca cacique of Turmequé between 1570 and 1590, this essay examines the stark disparity between the extensive documentation surrounding the cacique’s life—publicized by historian Ulises Rojas in 1965—and the prevailing interpretations about him. The historian’s hermeneutic suspicion ought to be reserved for historiography, not for the archives. In this instance, the documentation challenges canonical narratives of the colonial period on four fronts: the role of Indigenous children of Spaniards in the conquest; the origin of the “mestizo” category; colonial bureaucracy and Indigenous political agency; audits (visitas) and social mobility; and the knowledge and protagonism of the royal court and the Crown.